THE INFLUENCE OF FUNDRAISING, LEVEL OF FINANCIAL TRANSPARENCY, AND ORGANIZATIONAL REPUTATION ON THE LEVEL OF WAKIF'S TRUST IN PAYING AL-QUR'AN WAQF AT LAZIS NURUL FALAH SURABAYA WITH MOTIVATION AS A MODERATING VARIABLE - Lestari, Karisma Ratna; Amir, Faizal (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to evaluate the influence of fundraising, level of financial Transparency, and organizational Reputation on the level of wakif's trust in paying Al-Qur'an waqf at LAZIS Nurul Falah Surabaya. This study uses a quantitative method with moderation analysis using the Smart PLS 4 application in this study. For this study, a population of 183 was used and a sample of 126 wakifs using the accidental sampling technique. The results of the study indicate that in contrast to financial Transparency, which does not affect wakif's trust, the variables fundraising, organizational Reputation, and wakif's level of trust partially affect the interest in paying zakat. Moreover, fundraising, the level of financial Transparency, and organizational Reputation on the level of wakif's trust have a positive and significant effect on the interest in paying zakat, but in contrast to financial Transparency, which does not affect wakif's trust